Staff Profile: Christabel M. Eboso - Christabel, M. Eboso (UoEm, 2024)
■ Advocate of the High Court of Kenya, with over 5 years of experience in providing overall strategic and administrative leadership by supporting programs, providing technical expertise to consumers of legal services. ■ Gender Mobilizer, supporting gender advocacy activities, and capacity building for the youths, women, gender identity minorities and communities in collaboration with local, regional and international organizations on Health/Sexual and Reproductive Health and Rights, and influence health policy formulation and health advocacy ■ A researcher and scholar who develops policy and has published research on gender Justice and Women’s Rights under International conventions including the Maputo Protocol. ■ A transformational leader and teacher of the law who provides valuable perspectives to students, partners, and the Board – setting the vision, focus, and strategies to build and lead robust organizations. ■ Effective communicator with solid written and communication skills in English and Kiswahili, and technical proficiency in MS Office Suite.